Patient-centred outcomes following non-operative treatment or appendicectomy for uncomplicated acute appendicitis in children. Issue 1 (6th February 2023) - Hall, Nigel J; Sherratt, Frances C; Eaton, Simon; Walker, Erin; Chorozoglou, Maria; Beasant, Lucy; Stanton, Michael; Corbett, Harriet; Rex, Dean; Hutchings, Natalie; Dixon, Elizabeth; Crawley, Esther; et al.
Abstract : While non-operative treatment has emerged as an alternative to surgery for the treatment of uncomplicated acute appendicitis in children, comparative patient-centred outcomes are not well documented. We investigated these in a feasibility randomised trial. Of 57 randomised participants, data were available for 26. Compared with appendicectomy, children allocated to non-operative treatment reported higher short-term quality of life scores, shorter duration of requiring analgesia, more rapid return to normal activities and shorter parental absence from work. These preliminary data suggest differences exist in recovery profile and quality of life between these treatments that are important to measure in a larger RCT. Trial registration number is ISRCTN15830435 .